Crowdsourcing for Transit-Oriented Planning Projects: A Case Study of "inTeractive Somerville". - Messina, Michael. (2017)
Abstract: Since public participation was widely introduced into the planning process by advocacy planners in the 1960s there have been innovations and improvements. However, planners are continuously challenged with how to involve the public in the planning process. Some challenges of public participation include the dynamics of face-to-face politics, harnessing creative solutions and the one-way communication format. Other participation challenges include citizens having the "power" to make actual contributions to the plan. This thesis sought to explore the hypothesis that crowdsourcing is an appropriate model for enabling public participation in public planning projects. Through traditional and cutting-edge research methods, the findings of this case study suggest that crowdsourcing public participation has the ability to facilitate the planning process by generating more distinct ideas per participant than traditional participation and involving individuals in the planning process that do not typically participate. However, in the case study of inTeractive Somerville, crowdsourcing appears to be better suited to facilitate public participation focused on creating better and more widely accepted ideas and plans rather than public participation focused on upholding democratic principles.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Peter Levine.; Keywords: Urban planning, Information technology, and Transportation planning.